A Systematic Literature Review of Liquidity, Asset Quality, Efficiency, and Solvability of Profitability on Foreign Bank - Arie Dwi Kurniawati (IPTEK Journal of Proceedings Series, 2020)
An assessment of the performance of a foreign bank can be done by analyzing its financial statements. Financial performance of foreign banks in Indonesia when viewed from ROA has not been satisfactory. The aim of this study is to analyze whether the LDR, NPL, BOPO, and CAR have significant influence simultaneously and partially to ROA foreign banks. The paper is conceptual and qualitative in nature. This study examines 8 previous studies that discussed the effect of liquidity, asset quality, efficiency and solvability of profitability in banks.The Study followed a descriptive research design and used secondary data obtained from the company annual reports and partly from the foreign bank. There are one basic theory about signaling theory and previous research found some propositions : 1) LDR have significant effect to ROA, 2) NPL have significant effect to ROA, 3) BOPO have significant effect to ROA, 4) CAR have significant effect to ROA. The implication of this research can be used as input for banks in managing business risk in an effort to obtain the expected level of profit